2016
DOI: 10.17576/3l-2016-2202-11
|View full text |Cite
|
Sign up to set email alerts
|

Tracing Developmental Changes in L2 Learners’ Structuring of Phrasal Verbs: A Corpus Study of Native and Non-native Argumentative Essays

Abstract: This study investigates the production patterns of English phrasal verbs (PV) by Korean-speaking

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…An in-depth analysis was undertaken by Arabi and Ali (2015), where they found that tertiary-level EFL students are unable to recognizably distinguish between given and new topic information within written text (Petch-Tyson, 2014;Sung & Kim, 2016), and that they demonstrate weakness in achieving coherent flow of topic information within academic text (Fitriati & Yonata, 2017). Studies have also found that tertiary-level EFL students have difficulty using certain connective discourse markers to continue given to new topic information flow within academic writing (Farnia & Barati, 2017;Nguyen Thi Thuy, 2018;Prasithrathsint, 2015;Sato, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An in-depth analysis was undertaken by Arabi and Ali (2015), where they found that tertiary-level EFL students are unable to recognizably distinguish between given and new topic information within written text (Petch-Tyson, 2014;Sung & Kim, 2016), and that they demonstrate weakness in achieving coherent flow of topic information within academic text (Fitriati & Yonata, 2017). Studies have also found that tertiary-level EFL students have difficulty using certain connective discourse markers to continue given to new topic information flow within academic writing (Farnia & Barati, 2017;Nguyen Thi Thuy, 2018;Prasithrathsint, 2015;Sato, 2019).…”
Section: Introductionmentioning
confidence: 99%